Effect of Applied Potential on the Formation of Self-Organized TiO2 Nanotube Arrays and Its Photoelectrochemical Response - Chin, Wei Lai; Sreekantan, Srimala (Hindawi Publishing Corporation, 2011)
Self-organized TiO2 nanotube arrays have been fabricated by anodization of Ti foil in an electrochemical bath consisting of 1Mof glycerol with 0.5wt% ofNH4F. The effects of applied potential on the resulting nanotubes were illustrated. Among all of the applied potentials, 30 V resulted in the highest uniformity and aspect ratio TiO2 nanotube arrays with the tube’s length approximately 1 μm and pore’s size of 85 nm. TiO2 nanotube arrays were amorphous in as-anodized condition. The anatase phase was observed after annealing at 400◦C in air atmosphere. The effect of crystallization and effective surface area of TiO2 nanotube arrays in connection with the photoelectrochemical response was reported. Photoelectrochemical response under illumination was enhanced by using the annealed TiO2 nanotube arrays which have larger effective surface area to promote more photoinduced electrons.